Corporate Governance Failure: The Case Of Enron And Parmalat - Dibra, Rezart (European Scientific Journal, ESJ, 2016)
Corporate governance is a central and dynamic aspect of business. The term governance is derived from the latin word gubernare, meaning to steer. It usually applies to the steering of a ship. Thus, this implies that corporate governance involves the function of direction rather than control. Corporate governance has come to the forefront of academic research due to the vital role it plays in the overall health of economic systems. Corporate governance was long ignored as a matter of potential importance for the development of a nation’s economy. The wave of U.S. corporate fraud in the 1990s was attributed to deficiencies in corporate governance. The recent 2008-2009 global financial crisis, triggered by the unprecedented failure of Lehman Brothers and the subprime mortgage problems, renewed interest on the role of corporate governance in the financial sector. The development of a strong corporate governance framework is important to protect stakeholders, maintain investor confidence in the transition countries, and attract foreign direct investment. This paper looks at the collapse of Enron and the Parmalat, which was a particular Italian scandal. Parmalat, Enron, and other American firms such as Tyco and WorldCom all have a number of fudging at their core – efforts to make the companies look healthier than they were. Parmalat’s collapse began in November when its auditor raised questions about a $135 million derivatives profit. After additional evidence of accounting misstatements, the company’s chief executive and founder, Calisto Tanzi, resigned on the 15th of December. Four days later, the company disclosed the fake Bank of America letter. On the 23rd of December, Italian investigators stated that the company had used dozens of offshore companies to report non-existent assets to offset themselves. This was as much as $11 billion in liabilities. Also, this is in addition to the fact that Parmalat might have been falsifying its accounting figures for as long as 15 years.